ANALYSIS OF RISK FACTORS ASSOCIATED WITH THE INCIDENCE OF CHRONIC KIDNEY DISEASE IN INDONESIA - Ibrahim, Fauziah; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Chronic kidney disease is a condition that occurs due to decreased kidney function to maintain body balance. Chronic kidney disease has become a worldwide medical problem caused by the ever-increasing prevalence and number of deaths. In addition, chronic kidney disease also has a poor prognosis and poses a high burden of health costs for the country. So preventive measures are needed. One of them is by knowing the risk factors associated with the disease. The goal of this literature review is to specify what risk factors are connecting with the incidence of chronic kidney disease in Indonesia. In this literature review the collection of relevant articles or journals obtained in the Google Scholar and Pubmed databases. Which is done systematically by following the correct stages using the Prism format and determining inclusion and exclusion criteria. Based on the results of the analysis, 9 journals were obtained that explain the risk factors connecting with the case of chronic kidney disease in Indonesia. The Risk factors are hypertension, diabetes mellitus, urinary organ disorders, consumption of nonsteroidal anti-inflammatory drugs (NSAIDs), family history of chronic kidney disease, age, sex, and history of cardiovascular disease. Conclusion There are factors that are closely related are hypertension, diabetes mellitus, urinary tract disorders and consumption of non-steroidal anti-inflammatory drugs (NSAIDs). Keywords: Risk Factors, Chronic Kidney Disease, Indonesian